Pembelajaran Inkuiri Melalui Media Loose Parts untuk Mengembangkan Sains di PAUD Terpadu Syaiful Jannah Tanah Datar - Ersiyoma, Nidia; Suryana, Dadan (Jurnal Family Education, 2022)
This research is motivated by the lack of children’s scientific ability in expressing their ideas independently without the help of the teacher. This can be seen from the children’s lack of interest in completing the activities designed by the teacher. The purpose of this research will be to use quantitative methods in the aplication inquiry learning through loose parts media to children aged 5-6 years. The number of research subjects was 14 children, 7 children in class B1, 7 children in class B2 os Syaiful Jannah Integrated PAUD in Tanah Datar Regency. Data collectiom techniques were carried out through observation and documentation methods. The instrument used is a test of learning outcomes. Which consists of pre-test and post-test, and treatments 1, 2, and 3. After analyzing the data, the results of the hypothesis test are 0,001 which is smaller than 0,05. This is said because there is a difference between the sciencetific abilities of the children in the experimental group using direct practice methods with loose parts media and the control group carrying out learning activities according to the RPPH designed by the teacher in the class.